Structural Styles and their Suitability for Hydrocarbon in Eastern Sindh Monocline, Lower Indus Basin, Pakistan - Khaskheli, Mujeeb Rehman; Agheem, Muhammad Hassan; Panhwar, Manzoor Ali; Akram, Ulfat; Nazir, Jabir (International Journal of Economic and Environmental Geology, 2023)
The present study is aimed to recognize the structural styles of hydrocarbon exploration and petrophysical properties of the LGF. The 2-D seismic and well log data set is composed of three seismic lines and well log data of Chak 66–1. Five horizons have been marked with the help of well to seismic tie namely tops of Ranikot, Parh, upper Goru, lower Goru, basal and top massive sands, and out of which basal and massive sands are the objective focus of the present study. Based on seismic data, the study area is characterized by normal faults showing NW–SE dipping trend. Horst and graben structural features are prominent on the seismic lines, which indicated the extensional tectonic regime. Time–depth contour maps and 3D surfaces of objective horizons depict their actual spatial distribution in this area. Wireline logging analysis revealed the physical properties of both basal and massive grains of sand, as 17% effective porosity, 25% average volume of shale (Vsh), 40% water and 60% hydrocarbon saturations for basal sands, Whereas, 16% effective porosity, 35% Vsh, 30% water and 70% hydrocarbon saturations are interpreted for massive sands. Cross–plots of Nphi–Dt and Dt–Rhob also identified that both areas of sand are clean, gas–saturated and have the potential to produce hydrocarbons.